Gentamicin Susceptibility in Neisseria gonorrhoeae and Treatment Outcomes for Urogenital Gonorrhea After 25 Years of Sustained Gentamicin Use in Malawi. Issue 4 (12th April 2022) - Matoga, Mitch; Chen, Jane S.; Krysiak, Robert; Ndalama, Beatrice; Massa, Cecilia; Bonongwe, Naomi; Mathiya, Esther; Kamtambe, Blessing; Jere, Edward; Chikaonda, Tarsizio; Golparian, Daniel; Unemo, Magnus; et al.
Abstract : Gentamicin Etest minimum inhibitory concentrations suggest continued susceptibility against urogenital Neisseria gonorrhoeae in Malawi, but clinical failures to cure infection are detected. First-line treatment of N. gonorrhoeae in Malawi should be reassessed. Abstract : Background: Gentamicin has been used for the treatment of gonorrhea in Malawi since 1993. However, declining clinical cure rates have been suspected. We evaluated current Neisseria gonorrhoeae susceptibility to gentamicin in vitro and clinically. Methods: Men with acute urethritis were recruited at the Bwaila District Hospital STI Clinic in Lilongwe, Malawi, between January 2017 and August 2019. All men provided urethral swabs for etiological testing at enrollment and test of cure (TOC), 1 week later, using Gram-stained microscopy and culture. We used Etest to determine minimum inhibitory concentrations (MICs) of gentamicin, azithromycin, cefixime, ceftriaxone, ciprofloxacin, and spectinomycin; disc diffusion for tetracycline susceptibility; and whole-genome sequencing (WGS) to verify/refute treatment failure. Results: Among 183 N. gonorrhoeae culture-positive men enrolled, 151 (82.5%) had a swab taken for TOC. Of these 151 men, 16 (10.6%) had a positive culture at TOC. One hundred forty-one baseline isolates were tested for gentamicin susceptibility using Etest: 2 (1.4%), MIC = 2 μg/mL; 111 (78.7%), MIC = 4 μg/mL; and 28 (19.9%), MIC = 8 μg/mL. All isolates were susceptible to azithromycin, cefixime, ceftriaxone, and spectinomycin, whereas 63.1% had intermediate susceptibility or resistance to ciprofloxacin. Almost all (96.1%) isolates were resistant to tetracycline. All examined isolates cultured at TOC (n = 13) had gentamicin MICs ≤8 μg/mL. Ten men had pretreatment and posttreatment isolates examined by whole-genome sequencing; 2 (20%) were verified new infections (4119 and 1272 single-nucleotide polymorphisms), whereas 8 (80%) were confirmed treatment failures (0–1 single-nucleotide polymorphism). Conclusions: Gentamicin MICs poorly predict gonorrhea treatment outcome with gentamicin, and treatment failures are verified with gonococcal strains with in vitro susceptibility to gentamicin. The first-line treatment of gonorrhea in Malawi should be reassessed.